Penyiram Tanaman Otomatis Berbasis Informasi Sinyal Sensor Kelembaban - Anton Yudhana; Muhamad Caesar Febriansyah Putra (Annual Research Seminar (ARS), 2016)
Abstract— Tomato plants could grow well in the dry season. The water content will affect the growth and fruit quality. Tomatoes is a horticultural farm commodities, which focuses on the cultivation of fruit crops using pot by utilizing small area around the home. This research focused on designed tool uses automatic watering system in the form of work with input sensor signal based on soil moisture. The core of this plant sprinklers using ATMEGA8535 that controls the relay as a contactor for pump the water. The results of this study indicated that the experiments were conducted to make comparisons between water masses with a mass of soil (soil mass in dry conditions) produced an average of differences in measurement results from instruments made against ASM (American Standard Method) amounted to 4.391%. Measurement subsequent experiments ranging from the initial state of the water supply to the water pump goes out the initial state of the sensor readings to a tomato plant is a dry water content = 29.8% Vin = 3.35 Volts to wet conditions or passing of water content is determined that the moisture content = 83.3 % Vin = 1.20 Volt.